Density functional theory simulation of cobalt oxide aggregation and facile synthesis of a cobalt oxide, gold and multiwalled carbon nanotube based ternary composite for a high performance supercapattery - Iqbal, Javed; Li, Lijie; Numan, Arshid; Rafique, Saqib; Jafer, Rashida; Mohamad, Sharifah; Khalid, Mohammad; Ramesh, Kasi; Ramesh, Subramaniam (Royal Society of Chemistry, 2019)
A novel ternary composite consisting of cobalt oxide (Co3O4) nanoparticles (NPs) grown on multiwalled carbon nanotubes (MWCNTs) and mixed with gold (Au) NPs is synthesized by a single step hydrothermal route. Initially, density functional theory (DFT) simulations were carried out to model the aggregation of Co3O4 NPs and validated further with experimental results. To circumvent this issue, MWCNTs with gold NPs were introduced, which significantly reduced the particle aggregation. Standard three electrode cell studies revealed that the Co3O4/Au@MWCNT composite possesses an excellent energy density, rate capability and very good cyclic stability compared to unsupported Co3O4 or the binary Co3O4@MWCNT. The promising electrochemical performance compared to the single Co3O4 or the binary Co3O4@MWCNT materials is assigned to the synergetic effects of MWCNTs and Au to disaggregate the Co3O4 NPs and to enhance the overall conductivity, respectively. In order to get insight into the evaluation of the performance, two electrode devices were assembled employing activated carbon as a negative electrode and the Co3O4/Au@MWCNT composite as a positive electrode material. The two electrode supercapattery device demonstrated splendid cycling stability with a retention value of 91.90% in 1 M KOH for over 3500 cycles. Additionally, it exhibited an excellent energy density of 18.80 W h kg-1 at a power density of 302.00 W kg-1. These encouraging outcomes can be associated with the distinctive morphology, outstanding conductive networks, increased electroactive sites, and emergence of strong networking of Co3O4, MWCNT and Au in the ternary composite. This journal is © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.